Proposed Authentication Platform for E-Voting IoT System - Salman Mohsen, Ahmed; Ibrahim Shujaa, Mohamed; Bahaaulddin A. Wahhab, Ahmed (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In recent years, traditional elections have failed to satisfy public and political authorities. The traditional elections paper based is suffering from many issues of cheating the ballots or spoilage of the election documents. As a result to these mentioned issues many countries go forward adopting the electronic voting system to tackle the issues of traditional voting. Elections aren’t entirely safe because votes can be easily hacked. It also jeopardizes voter privacy and transparency. Furthermore, counting the ballots takes far too long. This paper suggests a Blockchain-based solution to address all of the problems of traditional elections. Theoretically, vote security, authentication, and data integrity are guaranteed. This research proposed a voting center by using and IOT point that saves the votes as a blockchain block attached to a blockchain. Because the data inside the blockchain is not encrypted so there is a need for encryption to ensure the privacy of the data in each block, accordingly the security is ensured by Speck cipher lightweight block cipher and bakers chaotic key generator to increase the safety of the information in each block (Vote). The reason behind choosing the lightweight is to operate the encryption method on IOT point with a limited hardware resources like Raspberry pi. The use of the blockchain as a secured public leader with a powerful hashing system with light weight speck cipher show a good improvement in block’s data integrity and privacy. Authentication is also provided using a fingerprint logging system. The authentication fingerprint system was accurate and efficient. The proposed e-voting system lets voters Vote either in-office or elsewhere. Finally, the proposed Blockchain voting mechanism significantly reduced the time of creating blocks and encryption of data inside each block.